Biomaterials and bioengineering to guide tissue morphogenesis in epithelial organoids - Jeon, Eun Young; Sorrells, Leila; Abaci, Hasan Erbil (Frontiers in Bioengineering and Biotechnology, 2022)
Organoids are self-organized and miniatured in vitro models of organs and recapitulate key aspects of organ architecture and function, leading to rapid progress in understanding tissue development and disease. However, current organoid culture systems lack accurate spatiotemporal control over biochemical and physical cues that occur during in vivo organogenesis and fail to recapitulate the complexity of organ development, causing the generation of immature organoids partially resembling tissues in vivo. Recent advances in biomaterials and microengineering technologies paved the way for better recapitulation of organ morphogenesis and the generation of anatomically-relevant organoids. For this, understanding the native ECM components and organization of a target organ is essential in providing rational design of extracellular scaffolds that support organoid growth and maturation similarly to the in vivo microenvironment. In this review, we focus on epithelial organoids that resemble the spatial distinct structure and function of organs lined with epithelial cells including intestine, skin, lung, liver, and kidney. We first discuss the ECM diversity and organization found in epithelial organs and provide an overview of developing hydrogel systems for epithelial organoid culture emphasizing their key parameters to determine cell fates. Finally, we review the recent advances in tissue engineering and microfabrication technologies including bioprinting and microfluidics to overcome the limitations of traditional organoid cultures. The integration of engineering methodologies with the organoid systems provides a novel approach for instructing organoid morphogenesis via precise spatiotemporal modulation of bioactive cues and the establishment of high-throughput screening platforms.